Flying under the radar: CDH2 (N-cadherin), an important hub molecule in neurodevelopmental and neurodegenerative diseases - László, Zsófia I.; Lele, Zsolt (Frontiers in Neuroscience, 2022)
CDH2 belongs to the classic cadherin family of Ca2+-dependent cell adhesion molecules with a meticulously described dual role in cell adhesion and beta-catenin signaling. During CNS development, CDH2 is involved in a wide range of processes including maintenance of neuroepithelial integrity, neural tube closure (neurulation), confinement of radial glia progenitor cells (RGPCs) to the ventricular zone and maintaining their proliferation-differentiation balance, postmitotic neural precursor migration, axon guidance, synaptic development and maintenance. Despite its vital importance, genetic links between CDH2 and neurodevelopmental and/or neurodegenerative diseases have been scarce. This, however, has changed significantly in the last few years and in this review, we summarize recent developments regarding CDH2 function and its involvement in pathological alterations of the CNS.